Challenges and Opportunities of Online Education during Covid-19 Situation in Nepal (Rupantaran: A Multidisciplinary Journal, 2021)
Nearly all governments around the world have temporarily closed educational institutions due to Covid-19 pandemic which are affecting up to 60% of the world’s student. Around, near to 200 countries closed their schools are interrupting the education of more than 1.5 billion young people and impact in long-term social and economic consequences. The aim of the meta-analysis is to evaluate the challenges and opportunities of online education during Covid-19 situation in Nepal by performing a systematic Meta analysis of related published literature. The Meta analysis was done diverse subjects and diverse research design was eligible among the 11 full-text articles. A formal extraction protocol was the PRISMA-P. Main finding of analysis is to offer an opportunity to shift to online learning and interaction and use virtual platforms for e-conference, webinars, podcasts, online class/ online-lectures etc. Opportunities for being continuations of academic career from any part of country; increase learning outcome among job holders. The changes in education technique, modality and process, which may required extra effort initially, provides teacher, faculty and facilitator the forcedly to keep pace with current trends in technology. This study recognized challenges as unequal access and quality of internet conveniences; affordability of laptops/computers; limited interaction; and frequent disturbances.